Numerical simulations of fatigue failure processes in intermittent jointed rock masses under the action of repeated stress waves - Ma, Shuyin; Xue, Sheng; Pan, Cheng (Frontiers in Earth Science, 2023)
In order to study the fatigue failure of intermittent jointed rock mass under repeated stress waves, the numerical models of jointed rock masses with various angles are built in the AUTODYN software, and crack propagation behavior is simulated using the Drucker-Prager strength model and cumulative damage failure criterion. In the numerical simulation, the influence factors on the fatigue failure of the rock mass, such as stress wave amplitude and the mode of disturbance, are analyzed. According to the simulation results, there is a significant difference between the failure process of jointed rock masses when subjected to repeated stress waves versus single stress waves, including crack initiation locations, propagation paths, and rock mass failure patterns. With increasing the angle of inclination, the fatigue life of rock mass first decreases and then increases under repeated stress waves. As the joint inclination angle of β ranging from 20o to 50o, it has a significant influence on the fatigue life of rock mass, and the fatigue life of rock mass decreases rapidly with the increase in joint angle β. Moreover, the variation of the disturbance form (the change in amplitude of the stress waves from small to large, or from large to small) does not affect the final macro failure pattern of rock mass, but the damage extent of rock mass is affected.